Service quality, customer satisfaction and customer loyalty : an SMRT perspective. - Chan, Huah Jer. (2008)
An analysis of the relationships between service quality and customer satisfaction, as well as customer satisfaction and customer loyalty, using the Singapore Mass Rapid Transit System (SMRT) as a case study.